O uso das estratégias de leitura com o gênero notícia: uma experiência no 9º ano do ensino fundamental - Barros , Andréa Regina Bezerril (2024)
The development of reading competence is essential in the context of Basic Education, considering that, as an instrument of social inclusion, reading allows students to acquire and expand their knowledge, being able to provide them with a critical view and action on the world, autonomously. However, one of the school's greatest challenges is precisely the training of a proficient reader, notably in Portuguese language classes. From our experience in the classroom, it is possible to see the difficulties in developing reading in Elementary School in the Final Years; consequently, training readers becomes more complicated. Based on this assumption, the proposal of this work is to present a reading project based on the journalistic news discursive genre, which was carried out in the 9th year of Elementary School, in a public school in the state of Rio Grande do Norte. This research is based on a diagnostic activity that was applied to the group of participating students, in order to analyze the main difficulties expressed by the students, and which included the application of reading workshops. As a theoretical contribution to support the work, we refer to the reading concepts of the authors Koch and Elias (2008), Bonifácio (2015), Cavalcante (2013) and Leffa (1996). Regarding reading strategies, we rely on Solé (1998) and Kleiman (2011); regarding discursive genres, we anchored ourselves in Bakhtin (2011) and Marcuschi (2008); We also seek guidance from official curricular documents proposed for Elementary Education, such as the Portuguese Language National Curricular Parameters - PCN-LP (1998) and the National Common Curricular Base - BNCC (2017). Regarding methodology, our research is applied in nature and interventionist in nature, characterized as action research, with a predominantly qualitative approach. After analyzing the three workshops carried out, taking the initial diagnostic activity as a starting point, making a comparative analysis with the final diagnostic activity, we noticed progress in students in relation to reading and understanding texts. They not only extracted information, but also began to make inferences, summarizes, formulate questions, elaborate answers and identify implicit and explicit ideas in the texts. Furthermore, they showed interest in reading in class. These positive advances motivate us to continue our research and actions aimed at developing our students reading skills. The activities proposed during the intervention were centered on the characteristics of the news genre, based on the perspective of conceptions and reading strategies and on the systematization of the study of the discursive genre through reading workshops that favored the understanding of the news.